Pantoprazole Induced Thrombocytopenia: a Case report - Mishra, Deebya Raj; Dahal, K.; Gupta, P.P. (Journal of BP Koirala Institute of Health Sciences, 2018)
Proton Pump Inhibitors serve as the cornerstone of management of Upper Gastrointestinal bleeding. In Nepal, intravenous Pantoprazole is widely used. One of the rare complications of intravenous Pantoprazole is thrombocytopenia which may lead to paradoxical increase in bleeding possibility. Here, we present a 70 year old gentleman who presented with hematemesis and melena and was treated with IV Pantoprazole. The Platelet count started decreasing from the third day onwards following which the patient was switched to Rabeprazole on the fourth day. Platelet count subsequently normalized. Thus, drug induced thrombocytopenia is one of the rare complications that has to be kept in mind with the use of Pantoprazole.